Tourism and the Environment in the Caribbean : An Economic Framework - Dixon, John; Hamilton, Kirk; Pagiola, Stefano; Segnestam, Lisa (World Bank, Washington, DC, 2014)
While tourism is one of the most important economic activities in the Caribbean, its reliance is based uniquely on the natural environment, indicating the resource base upon which all of this economic activity is based, is however fragile. Thus, sustainable tourism, and its economic benefits require ensuring that the environmental resources the sector relies on, are managed responsibly by the countries of the Caribbean, the tourism/travel industry, and the visitors themselves. The study examines the links between tourism, and environment, pointing at the magnitude of environmental threats, and the role of information, at creating strong incentives, addressing environmental problems certification schemes, to allow credible advertisement of its environmental quality. Capturing tourism economic "rents" - defined as an excess return to an asset - is viewed as a policy question for governments, on how to use these rents effectively. Mechanisms to capture rents include charging user fees when accessing a particular environmental resource, however, when environmental resources are public goods, user fees do not provide a practical means of capturing generated rents, thus more general taxation schemes are required. Based on this analysis, recommendations include the establishment of corporate income taxes, and moderate tariff rates for tourism inputs, establishing taxation, to be partly, and explicitly identified for environmental, and/or resource user fees.